Digitalisasi Laporan Piket Guru untuk Efisiensi Administrasi Sekolah - Rizqi Elmuna Hidayah; Rahmadi Agus; Jauhari Maulani; Muhammad Amin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The objective of this service activity is to enhance the efficacy of school administration through the digitalization of the picket teacher reporting system. The methodology employed entails the integration of Google Form-based technology with Autocrat, a supplementary application within Google Workspace that facilitates the automated generation of PDF reports based on user input data. This system replaces the manual recording method, which is considered less efficient and has a high risk of data loss. The implementation process was conducted through direct socialisation to teachers, as well as technical assistance in the management of the system. The findings of the activity demonstrate that the implementation of this digital system has the potential to expedite the reporting process, mitigate recording errors, and streamline the archiving and distribution of picket teacher reports. This finding demonstrates that the integration of simple technology can significantly impact the facilitation of more modern and efficient school administration governance. Abstrak Kegiatan pengabdian ini bertujuan mengoptimalkan efisiensi administrasi sekolah melalui digitalisasi pelaporan guru piket. Metode yang digunakan adalah implementasi Google Form yang terintegrasi dengan Autocrat untuk menghasilkan laporan otomatis dalam format PDF. Sistem ini menggantikan pencatatan manual yang kurang efisien dan rawan kehilangan data. Pelaksanaan dilakukan melalui sosialisasi dan pendampingan teknis kepada guru. Hasil menunjukkan peningkatan signifikan pada kecepatan pelaporan (87% responden), kemudahan penggunaan (93%), dan kerapian serta kemudahan akses arsip (100%). Temuan ini menegaskan bahwa integrasi teknologi mampu mendukung tata kelola administrasi sekolah yang modern, efisien, dan terdokumentasi dengan baik.